The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1104/pp.16.01214
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon-Mediated Aluminum Tolerance through Enhanced Expression of the Citrate Transporter OsFRDL4

Abstract: ORCID IDs: 0000-0003-3935-268X (K.Y.); 0000-0003-3411-827X (J.F.M.).High aluminum (Al) tolerance of rice (Oryza sativa) is controlled by multiple tolerance genes, but the regulatory mechanisms underlying the differential expression of these genes are poorly understood. Here, we investigated the factors regulating the expression of OsFRDL4, a gene encoding a citrate efflux transporter involved in Al-induced citrate secretion from the roots. Analysis with chromosome segment substitution lines derived from cv Nip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…In the present study, Al significantly induced the secretion of citrate (Figure 3A) and up-regulated the expression of OsFRDL4 (Figure 3B), which is able to transport citrate and correlates well with the secretion of citrate in rice (Yokosho et al, 2011, 2016). Elevated CO 2 had no further effect on the secretion of citrate in Al-treated plants (Figure 3A), indicating that citrate efflux does not contribute to the CO 2 -mediated reduction of Al accumulation in rice roots.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, Al significantly induced the secretion of citrate (Figure 3A) and up-regulated the expression of OsFRDL4 (Figure 3B), which is able to transport citrate and correlates well with the secretion of citrate in rice (Yokosho et al, 2011, 2016). Elevated CO 2 had no further effect on the secretion of citrate in Al-treated plants (Figure 3A), indicating that citrate efflux does not contribute to the CO 2 -mediated reduction of Al accumulation in rice roots.…”
Section: Discussionsupporting
confidence: 73%
“…The genes encoding organic acid (OA) transporter have been identified as important Al tolerance genes in various plants, and it has been demonstrated that the ELP of OA transporter caused by cis-element polymorphism is associated with the variation of Al tolerance among the accessions (Hoekenga et al, 2006;Sasaki et al, 2006;Magalhaes et al, 2007;Chen et al, 2013;Yokosho et al, 2016). The higher expression of the OA transporter gene has notably contributed toward high Al tolerance in various crops in the ELP.…”
Section: Gwas For Gene Expressionmentioning
confidence: 99%
“…OsFRDL4 encodes a Multidrug and Toxin Extrusion (MATE) transporter that mediates root citrate release (Yokosho et al, 2011); Al-activated release of organic acids from the root is a major physiological mechanism of plant Al resistance (Kochian et al, 2015). OsFRDL4 is the major candidate for the gene underlying an Al resistance QTL in a Nipponbare (temperate japonica) x Kasalath (aus) population (Yokosho et al, 2016). The authors of that study also reported a 1.2-Kb insertion in the promoter of OsFRDL4, and demonstrated that a majority of japonica varieties tested carried the insertion, while most indica varieties did not, and suggested that the insertion was associated with higher levels of OsFRDL4 expression under Al stress.…”
Section: Expression Of the Mate Transporter Osfrdl4 Is Dependent On Gmentioning
confidence: 99%
“…These "ART1-regulated genes" have received this denomination because they are mis-regulated in the art1 mutant; in other words, their expression is upregulated by Al stress in the wild type, but not in the mutant . It is worth noting that direct binding of the ART1 protein to upstream regulatory regions has so far been experimentally demonstrated only for STAR1 (Tsutsui et al, 2011) and OsFRDL4 (Yokosho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%